Dimensionamiento de sistemas fotovoltaicos conectados a la red eléctrica en el Ecuador en baja tensión. - Romero Márquez, Christian Javier (2020)
The present degree research boards the basic and important knowledge about photovoltaic systems, from the operation of each component, arrangements between the different equipment, and essentially, it proposes a dimensioning methodology for these systems connected to the electrical network in Ecuador in low voltage (public network), taking into account the considerations and restrictions established in the resolution 042/18 by the Agencia de Regulación y Control de la Electricidad (ARCONEL) for the photovoltaic microgeneration. The dimensioning photovoltaic system proposal is the numeric calculation in order to establish the quantity of panels to use, the numeric calculation of the batteries in case of implementing them (hybrid systems), the determination of the electric protection to use, the electrical wiring dimensioning, the analysis among the equipment compatibility, electrical technical configurations between them, the analysis of the solar trajectory to mitigate the energetic losses due to shading and the suitable conditions for grounding in these systems. Similarly, in the present research, the different established methodologies about the dimensioning of the photovoltaic systems in different countries of the region in order to encompass all the factors that influence them are analyzed. Furthermore, a methodology about the economic analysis with the proposal of analyzing the profitability of photovoltaic systems in a set time will be established. Finally, this research is based on the quantitative and qualitative analysis considering everything about the dimensioning of the photovoltaic systems at the residential, commercial and industrial level, in low voltage, therefore, the kind of research scope is descriptive, deductive, and analytical.